Peningkatan Kapasitas Mahasiswa dalam Penulisan Skripsi melalui Pelatihan Microsoft Word dan Mendeley - Luky Vianika Sari; Rizqi Praimadi Rosalin Rosalin; Muhammad Syafiq Akmal; Muhammad Fahrurrozi (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
Writing a thesis is a crucial step in completing undergraduate studies. However, many students experience technical difficulties, particularly with document organization and citation management. This Community Service (PKM) activity aims to improve students' thesis writing skills through Microsoft Word and Mendeley training. The training was conducted online via Google Meet and was attended by final-year students from various study programs. The material covered organizing scientific documents using Microsoft Word features (headings, automatic table of contents, citation styles), as well as reference management using Mendeley. The implementation method involved material presentations, live demonstrations, and real-time guided independent practice sessions. Evaluation results showed an increase in participants' understanding of the use of applications to support scientific writing. This activity significantly contributed to preparing students for the thesis writing process more systematically and efficiently.